Ecoprint as a Learning Media Based on Ceativity and Entrepreneurship in PKK Subjects at SMK Negeri 4 Gorontalo City - Hasmah Lagau; Ulin Naini; Ginarsyah Triyana Dewi Pau (HomeEC, 2026)
This study aims to describe ecoprint learning as an effort to develop vocational high school students’ skills and aesthetic abilities. This study employed a descriptive method with a quantitative approach. The sample consisted of 10 eleventh-grade students from the Creative Batik and Textile Craft specialization at SMK Negeri 4 Kota Gorontalo. Data were collected through observation, interviews, practical activities, and documentation. The data were analyzed using percentage techniques to determine students’ achievement in producing ecoprint works based on three assessment aspects: skills, aesthetics, and neatness. The results show that ecoprint learning supports the development of students’ technical skills in the production process and their aesthetic ability in arranging motifs and visual compositions. Overall, students’ ecoprint works were categorized as good to very good. Eight students obtained scores ranging from 80 to 89, categorized as good, while two students obtained scores ranging from 90 to 100, categorized as very good. The average score for the skill aspect was 87.3, the aesthetic aspect was 87.8, and the neatness aspect was 85.3. These findings indicate that ecoprint learning can be used as an effective alternative practical learning activity to develop students’ skills and aesthetic abilities in vocational education.